The Use Social Media For The Continuity Of The Covid 19 Pandemic Era Business - Yayuk Yuliana; Vera Kristiana (Ilomata International Journal of Management, 2021)
Pandemic Covid - 19 to share the impact that beyond the usual to the various areas, especially the zone 's economy , businesses Trigona stone frog that role is shared contribution that goodly great against the restoration of health is not separated affected from pandemic Covid - 19, in the study is looking at all where utilization social media face book for the sustainability of the business of aquaculture Trigona stone frog amid the pandemic Covid - 19. The study is wearing the procedure qualitative with approach of phenomenology . The study is to verify if the use of social media facebook that attempted by the group cultivation Trigona has suitable procedure is not only the Digital marketing has shared a positive impact amid the Covid -19 pandemic on the economic resilience of the trigona stone frog business by always carrying out the process of creating and distributing objects to consumers but always complying with the provisions of Social Distancing where . The use of media social via facebook calculated need for applied especially in the middle of the Pandemic Covid - 19 for reducing the loss of context with consumers but business is always running . Keywords : Pandemic Covid- 19, Facebook, Trigona